Strategi Peningkatan Kualitas Produk Sayuran Segar Organik pada CV. Golden Leaf Farm Bali - Anom Yuarini, Dewa Ayu; Satriawan, I Ketut; Oka Suardi, I Dewa Putu (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2015)
As one of the popular tourist attraction, the number of visitor in Bali has been increased every years, and the number of foreign tourist stayed in Bali has been increased either. This condition has given the positive impact to the restaurant, and other facilities which is support the tourism services. Tourism industry needs vegetables with the healthy quality, fresh, clean, and with the continuously safety guarantee on it. This situation has grown the chance to conserve the vegetables with the organic system. The main objective of this research are, (1) understanding the consumer’s wishes upon the quality of the fresh organic vegetables. (2) understanding the consumers satisfaction on the fresh vegetable organic; and (3) to formulate the strategy in improving the quality products of organic fresh vegetable. This research has been conducted in CV Golden Leaf Farm. CV GLF is a agroindustry organic vegetables company located at Asah Gobleg main street,Wanagiri village, Sukasada Distric, Buleleng Regency. And the method has been used in this research is the quality function deployment (QFD). QFD has the function to define all the consumer wishes on vegetables related to existances of parameter methodology in the company. In order to understanding the way to fulfill the highest consumer’s wishes. The result of this research shows the specification of the consumer wishes upon the organic vegetables products quality on CV. GLF are the cleanness, the freshness, and the food safety. The length period, color, size, and the standardization form of the products on CV . GLF has generated the number of consumer with the satisfaction categories such satisfy and fully satisfy. The satisfaction category has been reached by the attributed of freshness, size, color, the length period, food safety, and the shape standardization. While the cleanness attributes has included into the satisfaction categories. The strategy to improve the fresh organic quality of vegetable in CV,GLF are, a) To fulfill the consumer satisfaction, the attribute priority which necessary being revised or being evaluated are the attribute in the length period of the fruit, size, the shape standardization, color, the food safety, and the freshness, and b) to improve the consumer satisfaction upon the quality of vegetables quality so the technique  of parameter quality should be revised is the way of permanent saving quality, the cleansing, packaging, and sortation.
Keywords: quality function deployment (QFD), fresh organic vegetables, consumer satisfaction, strategy